A case report of arterial and venous thromboembolism in a patient with severe COVID-19 pneumonia. Issue 6 (17th November 2020) - Del Castillo-García, Samuel; Minguito-Carazo, Carlos; Echarte, Julio César; Rodríguez-Santamarta, Miguel; González, Tomás Benito; Terroba Seara, Sandra; Martìnez González, Lara; Fernández-Vázquez, Felipe
Abstract: Background: Coronavirus disease 2019 (COVID-19) has spread rapidly worldwide since the outbreak originated in Wuhan, China in December 2019. Cardiovascular complications in patients with severe COVID-19 have been reported and are associated with a worse outcome. Coagulopathy is one of the most common life-threatening complication increasing mortality; however, little evidence is available regarding prevention strategies or its treatment in COVID-19 patients. Case summary: We report a case of a 70-year-old woman admitted to hospital with severe COVID-19 bilateral pneumonia who developed severe coagulopathy with multiple both, venous and arterial, embolisms in major vessels such as bilateral pulmonary embolism, acute thrombus in abdominal aorta, and acute thrombotic occlusion of the right iliac common artery. The patient underwent emergent surgical thrombectomy of the right lower limb; in spite of anticoagulant treatment at therapeutic doses, patient presented poor clinical evolution and an infracondylar amputation of right lower limb was made finally. Subsequently, the patient received low molecular weight heparin (LMWH), antibiotics and antiviral therapy improving her renal function and her pneumonia, so she could be discharged safely. Discussion: Prothrombotic coagulopathy due to enhanced acute inflammatory response and diffuse intravascular coagulation has been described in severe critical COVID-19 patients. This state of hypercoagulability is associated with organ dysfunction and mortality and may predispose to both, venous and arterial, thromboembolism. Little data are available regarding the best therapeutic and prevention strategies in this scenario, although thrombosis prophylaxis with LMWH has been associated with a better outcome.